Teaching French Language Through Films: The Cultural Contents in French and Francophone Films - Tjahjani, Joesana; Jinanto, Damar (Universitas Pendidikan Indonesia, 2021)
Foreign language teaching in the current globalization era needs to compete with technological development. This competition is related to the discovery of digital technology-based methods to motivate learners to provide more interesting cultural content in language classes. For teachers from different cultural backgrounds, authentic documents such as films are considered very effective in delivering cultural content. This research takes a French film, Intouchables, and a Canadian francophone film, Monsieur Lazhar, as a research corpus for their cultural content to be analyzed. The proper understanding of the two films' cultural content can inform a digital technology-based French-language teaching medium. To discover what strategies or formulas are used in teaching French with cultural-laden films as teaching media requires studying the films by dissecting the structure of the text. Examination of the structure of the films was based on the theory of Boggs and Petrie (2008), equipped with in-depth reading to find signs in the text by referring to Buckland (2004); and also the identification of cultural content using the cultural approach by Stern (1992). The construction of a teaching plan with a language teaching approach by Damen (1987) and Byram (1997) will be the last step. This research provides an academic outcome that is a film structural analysis to identify cultural content in the two films. The second outcome is a practical categorization of cultural content utilized as a language teaching material.